2008
DOI: 10.1093/nar/gkn562
|View full text |Cite
|
Sign up to set email alerts
|

Rigid spin-labeled nucleoside Ç: a nonperturbing EPR probe of nucleic acid conformation

Abstract: Rigid spin-labeled nucleoside Ç, an analog of deoxycytidine that base-pairs with deoxyguanosine, was incorporated into DNA oligomers by chemical synthesis. Thermal denaturation experiments and circular dichroism (CD) measurements showed that Ç has a negligible effect on DNA duplex stability and conformation. Nucleoside Ç was incorporated into several positions within single-stranded DNA oligomers that can adopt two hairpin conformations of similar energy, each of which contains a four-base loop. The relative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 50 publications
3
85
2
1
Order By: Relevance
“…885 The rigid spin-label cytosine analogue (40) has been synthesised and forms stable base pairs with guanine, and was used to study the motion within an oligonucleotides that can adopt two different hairpin conformations. 177 Raman spectroscopy has been used in a study with EM to investigate the global structure of DNA binding to the bacteriophage P22 terminase subunit. 847 Surface enhanced Raman spectroscopy (SERS) is a technique in which samples are adsorbed onto rough metal surfaces and relies upon the excitation of localised surface plasmons.…”
Section: Other Structural Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…885 The rigid spin-label cytosine analogue (40) has been synthesised and forms stable base pairs with guanine, and was used to study the motion within an oligonucleotides that can adopt two different hairpin conformations. 177 Raman spectroscopy has been used in a study with EM to investigate the global structure of DNA binding to the bacteriophage P22 terminase subunit. 847 Surface enhanced Raman spectroscopy (SERS) is a technique in which samples are adsorbed onto rough metal surfaces and relies upon the excitation of localised surface plasmons.…”
Section: Other Structural Methodsmentioning
confidence: 99%
“…The analogue (40) forms a specific base pair with dG, and the mobility of it in oligonucleotides can be monitored by EPR. 177 In addition, (40) is highly fluorescent when the nitroxide is reduced (sodium sulphide) and the fluorescent signal intensity is dependent upon the nature of its complementary base, thus it is suggested that it is possible to identify the opposing base from the fluorescent signal. 178,179 The expanded cytosine analogue (41) has been used for triplex stabilisation, as the extended aromatic ring system projects into the major groove and aids stability of a third strand by additional stacking interactions.…”
Section: Oligonucleotides Containing Modified Sugarsmentioning
confidence: 99%
“…Phosphoramidite 4 was used to synthesize several oligonulceotides for characterization of DNAs containing Ç [54]. Circular dicroism measurements showed characteristic spectra for B-form DNA.…”
Section: Synthesis Of Rigid Spin Labels For Nucleic Acidsmentioning
confidence: 99%
“…The fluorescent nucleoside is sensitive to its microenvironment and is able not only to detect mismatches, but also to identify the mismatched base [28,29]. The bifunctionality of the spectroscopic probe allows, for the first time, the use of the same nucleic acid sample for both EPR and fluorescence spectroscopies and has been applied for the study of the conformation and dynamics of hairpin loops [30,31] and the folding of a DNA aptamer that binds cocaine [32].…”
Section: Rigid Nitroxide Spin Label ç: a Fluorophore In Disguisementioning
confidence: 99%